Reactivity studies in water on the acid-catalysed dehydration of psicose compared to other ketohexoses into 5-hydroxymethylfurfural - van Putten, Robert-Jan; van der Waal, Jan C.; de Jong, Ed; Heeres, Hero J. (Carbohydrate research, 2017)
The conversion of the four possible ketohexoses (fructose, tagatose, sorbose and psicose) into 5-hydroxymethylfurfural (HMF) was explored in water using sulphuric acid as the catalyst (33 mM H2SO4, 120 °C). Significant differences in reactivity were observed and tagatose (48% conversion after 75 min) and psicose (35% conversion after 75 min) were clearly more reactive than fructose and sorbose (around 20% conversion after 75 min). The selectivity to HMF was found to be higher for fructose and psicose than for tagatose and sorbose. 2-Hydroxyacetylfuran (HAF) was shown to be a by-product for mainly sorbose and tagatose (as high as 2% yield). The results indicate that the relative orientation of the hydroxyl groups on C3 and C4 has a major effect on the reactivity and selectivity. This suggests that the dehydration towards HMF takes place via a mechanism with cyclic intermediates in which the C3C4 bond is fixed in a ring structure. A reaction mechanism involving a bicyclic structure is proposed to explain the formation of HAF. The reactivity of the sugars was significantly lower in water than previously observed in methanol. [Display omitted] •Hydroxyl group orientation on C3 and C4 determines ketose reactivity in dehydration.•This suggests a reaction mechanism with cyclic intermediates.•Psicose would be the most favourable substrate for HMF production.•The orientation of the C4 hydroxyl is key in 2-hydroxyacetylfuran formation.•The reactivity of psicose and tagatose affects their application as sweeteners.